#Covid4Rheum: an analytical twitter study in the time of the COVID-19 pandemic - Ruffer, Nikolas; Knitza, Johannes; Krusche, Martin (Rheumatology International, 2020)
Social media services, such as Twitter, offer great potential for a better understanding of rheumatic and musculoskeletal disorders (RMDs) and improved care in the field of rheumatology. This study examined the content and stakeholders associated with the Twitter hashtag #Covid4Rheum during the COVID-19 pandemic. The content analysis shows that Twitter connects stakeholders of the rheumatology community on a global level, reaching millions of users. Specifically, the use of hashtags on Twitter assists digital crowdsourcing projects and scientific collaboration, as exemplified by the COVID-19 Global Rheumatology Alliance registry. Moreover, Twitter facilitates the distribution of scientific content, such as guidelines or publications. Finally, digital data mining enables the identification of hot topics within the field of rheumatology.
CRIS-Team Scopus Importer:2020-10-09
Keywords: COVID-19; Hashtag; Rheumatology; SARS-CoV-2; Twitter